A systematic review of the implementation of the blackboard learning system as e-learning: opportunities and challenges to the online learning environment - Almijlad, Aliyah Kayyad (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Blackboard learning has particularly endorsed the use of e-learning operations. Although particular reference has been made to a certain internet application or service, the benefits and difficulties of implementing the blackboard scheme on online education have not been systematically understood. A review of the literature was therefore carried out to define the significant possibilities and challenges of studying the blackboard system to implement it as an e-learning system. The articles were selected from SCOPUS journals using the keywords "blackboard-based learning and interaction" and "blackboard-based learning and computer-based learning as internet learning" and a total of 430 articles were obtained and screened from the referenced databases. Finally, a total of 14 publications were chosen to evaluate information after inclusion and exclusion criteria in order to accomplish the primary goals of this research. The review findings revealed that a set of evidence supporting the use of blackboard learning system is efficient for geographically distant learners. Through this scheme, learners can share their thoughts with each other. Even though blackboard users and non-users have positive intention to implement this system and the system is suitable for enhancing students’ academic performance at all levels of education, the system is not presently used for teaching and learning by the big proportions of those who have undergone Blackboard trainings. This article also revealed the main possibilities and difficulties associated with using these systems in the teaching context of Blackboard. The Blackboard Learning System is an efficient way in the field of education to move towards more interactive and innovative internet learning settings.